Characterization of lymphangioleiomyomatosis patients with discordance between spirometric and diffusion measurements of pulmonary function - Courtwright, Andrew; Baldi, Bruno G. Baldi3 G; Kidambi, Pranav; Cui, Ye; Lamattina, Anthony M; Villalba, Julian A; Bagwe, Shefali; Goldberg, Hilary J; Rosas, Ivan O; Henske, Elizabeth Petri; Carvalho, Carlos R. R.; El-Chemaly, Souheil (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Background: A subset of lymphangioleiomyomatosis (LAM) patients present with normal FEV1 and FVC but with reduced DLCO.  Patients with an isolated reduction in DLCO in other diseases appear to be at higher risk for pulmonary hypertension and worse survival but this has not been previously described in LAM patients. Objective: To characterize the prevalence and clinical progression of LAM patients who present with discordantly low DLCO. Methods: This was a retrospective cohort study of LAM patients in two centers in the United States and Brazil. Discordant DLCO was defined as FEV1 >80% predicted, FVC >80% predicted, and DLCO1 (23.3% vs 20.1%, p=1.00). Patients with discordant DLCO did not have higher levels of VEGF-D (1214±1256 pg/mL vs 1706±1214 pg/mL, p=0.07). Conclusions: LAM patients who present with a discordantly low DLCO do not appear to have different rates of decline in pulmonary function. Additional biological and radiographic markers are needed to more fully characterize this population.